Evidence for strong and weak phenyl-C61-butyric acid methyl ester photodimer populations in organic solar cells - Pont,S; Osella,S; Smith,A; Marsh,AV; Li,Z; Beljonne,D; Cabral,JT; Durrant,JR (Chemistry of Materials, 2019)
In polymer/fullerene organic solar cells, the photochemical dimerization of phenyl-C61-butyric acid methyl ester (PCBM) was reported to have either a beneficial or a detrimental effect on device performance and stability. In this work, we investigate the behavior of such dimers by measuring the temperature dependence of the kinetics of PCBM de-dimerization as a function of prior light intensity and duration. Our data reveal the presence of both “weakly” and “strongly” bound dimers, with higher light intensities preferentially generating the latter. DFT simulations corroborate our experimental findings and suggest a distribution of dimer binding energies, correlated with the orientation of the fullerene tail with respect to the dimer bonds on the cage. These results provide a framework to rationalize the double-edged effects of PCBM dimerization on the stability of organic solar cells.